Development of BeBa (News Learning) Learning Media in News Text Learning - Putri, Aldila Rahmita; Zulfa, Lilis Anifiah (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
Learning news texts is one of the compulsory learning that students need to master. There are various factors that can affect the success of learning news texts. One of them is the use of learning media. This research and development aims to (1) develop BeBa (Belajar Berita) learning media in the material identifying elements of news texts for grade VIII students of SMPN 2 Sumbergempol, (2) testing the feasibility of BeBa (Belajar Berita) learning media in the material identifying elements of news texts for grade VIII students of SMPN 2 Sumbergempol. The ADDIE model is used in research and development of Beba learning media. There are two types of data obtained in this study. Qualitative data is obtained from interviews and comments or suggestions for improvement from students and validators. Quantitative data was obtained from the results of needs analysis questionnaires, material validator assessments, media validators, teacher practitioners, and student responses. The results of material validation by material experts obtained a percentage of 93.33% with the category "very feasible", the results of validation by media experts obtained a percentage of 96.88% with the category "very feasible", and the results of teacher assessment Indonesian obtained a percentage of 100% with the category "very feasible". The trials in this study were conducted twice, namely small group trials with 10 students obtaining a percentage of 98.45% with the category "very feasible" and large group trials with 25 students obtaining a percentage of 95.7% with the category "very feasible". Based on these results, the BeBa (Belajar Berita) learning media that has been developed has been tested for feasibility and is ready to be implemented in learning Indonesian class VIII news text materials.